Comprehensive comparative assessment of the Arabidopsis thaliana MLO2-CALMODULIN2 interaction by various in vitro and in vivo protein-protein interaction assays - von Bongartz, Kira; Sabelleck, Björn; Baquero Forero, Anežka; Kuhn, Hannah; Leissing, Franz; Panstruga, Ralph (The Biochemical journal, 2023)
Mildew resistance locus o (MLO) proteins are heptahelical integral membrane proteins of which some isoforms act as susceptibility factors for the powdery mildew pathogen. In many angiosperm plant species, loss-of-function mlo mutants confer durable broad-spectrum resistance against the fungal disease. Barley Mlo is known to interact via a cytosolic carboxyl-terminal domain with the intracellular calcium sensor calmodulin (CAM) in a calcium-dependent manner. Site-directed mutagenesis has revealed key amino acid residues in the barley Mlo calmodulin-binding domain (CAMBD) that, when mutated, affect the MLO-CAM association. We here tested the respective interaction between Arabidopsis thaliana MLO2 and CAM2 using seven different types of in vitro and in vivo protein-protein interaction assays. In each assay, we deployed a wild-type version of either the MLO2 carboxyl terminus (MLO2CT), harboring the CAMBD, or the MLO2 full-length protein and corresponding mutant variants in which two key residues within the CAMBD were substituted by non-functional amino acids. We focused in particular on the substitution of two hydrophobic amino acids (LW/RR mutant) and found in most protein-protein interaction experiments reduced binding of CAM2 to the corresponding MLO2/MLO2CT-LW/RR mutant variants in comparison with the respective wild-type versions. However, the Ura3-based yeast split-ubiquitin system and in planta bimolecular fluorescence complementation (BiFC) assays failed to indicate reduced CAM2 binding to the mutated CAMBD. Our data shed further light on the interaction of MLO and CAM proteins and provide a comprehensive comparative assessment of different types of protein-protein interaction assays with wild-type and mutant versions of an integral membrane protein.
Keywords: proteiny huseníčku; protein–protein interactions; Calmodulin; MLO; Arabidopsis; interakční proteinové domény a motivy; nemoci rostlin; kalmodulin; Protein Interaction Mapping; comparative analysis; Calcium; Arabidopsis Proteins; calmodulin; Protein Interaction Domains and Motifs; Plant Diseases; vápník; mapování interakce mezi proteiny